2011
DOI: 10.5171/2011.117860
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Mobile Money Implementation in Nigeria

Abstract: A sizeable number of people in developing nations, particularly Africa countries are rural dwellers who seldom have access to banking services despite their heavy reliance on remittances from economic migrants for social protection and poverty alleviation.There is therefore a dire need for the development of an effective mechanism for funds remittance especially for the rural dwellers. The development of mobile money (m-Money) will facilitate access to finance through the mobile platform, which has the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Primary research on mobile banking was conducted in the early 2000s [25]. The adoption of mobile banking and related services in developing economies has been studied [19] over the past years in countries such as: South Africa (MTN money, Wizzit), Kenya (mPESA), India (Eko) and in continents such as Asia (SmartMoney and G-Cash) [26][27][28][29][30]. However, studies about the elderly behaviour on mobile banking and commerce are rare [2,31], a few studies have examined ease of use and extrinsic and intrinsic motivations for the elderly's usage of mobile applications [32].…”
Section: Mobile Commerce and Bankingmentioning
confidence: 99%
“…Primary research on mobile banking was conducted in the early 2000s [25]. The adoption of mobile banking and related services in developing economies has been studied [19] over the past years in countries such as: South Africa (MTN money, Wizzit), Kenya (mPESA), India (Eko) and in continents such as Asia (SmartMoney and G-Cash) [26][27][28][29][30]. However, studies about the elderly behaviour on mobile banking and commerce are rare [2,31], a few studies have examined ease of use and extrinsic and intrinsic motivations for the elderly's usage of mobile applications [32].…”
Section: Mobile Commerce and Bankingmentioning
confidence: 99%
“…The Central Bank of Nigeria demonstrated keen interest because it saw such projects as an opportunity to drive development and modernization of the payment system, in line with Nigeria's vision of being among the top 20 economies in the world by 2020 [ 15 ]. Mobile money is a technology-assisted financial service delivered to the beneficiaries via mobile phone device [ 16 ]. A study on the adoption of mobile money in Nigeria revealed that culture is the most important factor influencing the adoption behavior of users of mobile banking in Nigeria [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Services encompass online transactions, mobile and prompt payments, electronic payment of bills, automatic clearance of cheques, ATMs (Automated Teller Machines) etc. Of these, researchers found that mobile payment was effective in alleviating poverty in rural areas of Nigeria (Ayo et al, 2011). So, what are the reasons for this development in Nigeria?…”
Section: Digital Saving Service In Nigeriamentioning
confidence: 99%